Scientific and technological communication. - Passman, Sidney (Pergamon Press, 1969)
Scientific and Technological Communication deals with the fundamental aspects of the elements and media of scientific and technological communication, with emphasis on the critical issues involving them as well as the opportunities and techniques for exploiting them. Topics covered include informal information exchange; specialized information and analysis centers; mechanization and information handling; and international aspects of scientific and technical communication. This book is comprised of nine chapters and begins with an overview of the scientific communication process, its evolution,